2020
DOI: 10.1002/bab.1925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel, cobalt, and iron on methanogenesis from methanol and cometabolic conversion of 1,2‐dichloroethene by Methanosarcina barkeri

Abstract: Methanogens are responsible for the last step in anaerobic digestion (AD), in which methane (a biofuel) is produced. Some methanogens can cometabolize chlorinated pollutants, contributing for their removal during AD. Methanogenic cofactors involved in cometabolic reductive dechlorination, such as F 430 and cobalamin, contain metal ions (nickel, cobalt, iron) in their structure. We hypothesized that the supplementation of trace metals could improve methane production and the cometabolic dechlorination of 1,2-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Since methanogens are known to be cometabolizers of chlorinated pollutants, Paulo et al. [5] focused their work on the effect of nickel, cobalt, and iron on the growth of Methanosarcina barkeri . The data show how metal addition improves 1,2‐dichloroethene dechlorination to vinyl chloride, indicating that metal ions can be a limiting factor in methanogenesis and dechlorination.…”
Section: Innovative Processes For the Production Of Bioethanol Butanmentioning
confidence: 99%
“…Since methanogens are known to be cometabolizers of chlorinated pollutants, Paulo et al. [5] focused their work on the effect of nickel, cobalt, and iron on the growth of Methanosarcina barkeri . The data show how metal addition improves 1,2‐dichloroethene dechlorination to vinyl chloride, indicating that metal ions can be a limiting factor in methanogenesis and dechlorination.…”
Section: Innovative Processes For the Production Of Bioethanol Butanmentioning
confidence: 99%
“…If methane production is intended, Fe(III) should be dosed to avoid out-competition of methanogens by IRB [ 21 ]. Moreover, amorphous Fe(OH) 3 was shown to directly inhibit the activity of Methanospirillum hungatei and Methanosaeta concilii grown in pure culture [ 22 ], and some methanogens (e.g., Methanosarcina barkeri ) also have the ability to reduce Fe(III), which may contribute to methanogenesis inhibition [ 22 , 23 ]. Bond and Lovley [ 24 ] reported that the inhibition of methane production in Fe(III) oxide-containing sediments may result, at least in part, from methanogens diverting electrons to Fe(III) reduction.…”
Section: Introductionmentioning
confidence: 99%